Forest and Society: Initiating a Southeast Asia Journal for Theoretical, Empirical, and Regional Scholarship - Fisher, Micah; Maryudi, Ahmad; Sahide, Muhammad Alif K. (Forestry Faculty, Universitas Hasanuddin, 2017)
Welcome to our first edition. We are excited to provide a new, and what we believe, timely avenue for presenting research findings and publications in Southeast Asia, for scholars interested in Southeast Asia. Although Southeast Asia as a region of study has provided tremendous contributions to theory and practice regarding forests and society across the social and natural sciences, avenues for cultivating a scholarship of the region remain limited. We seek to engage on a broad set of themes through the application of targeted research related to timely issues affecting the human-environment interface in a diverse region that we have much to learn from. We take a broad understanding of the forest - as a politico-administrative unit, a geographic area, and as an ecological unit. We do not limit the forest to its boundaries but rather seek to engage on the dynamics of change in social and ecological processes. Under such an umbrella, new approaches and methods become possible. 'Forest' can be analyzed as land use, ecological process, divided across watersheds, as landscapes, mountains, and more. The lens of 'society' allows for opportunities to understand change, whether it is the interaction between a resource to be preserved, exploited, forgotten, or erased. Forests, therefore, operate as the clues of what once was, has become, and what can be. Particularly in the age of climate change, riddled by increasingly complex challenges, a new dimension also emerges for the forest. Different perspectives at different scales - from the local to the global - provide equally important dimensions, and are those which we seek to provide avenues to learn from, and communicate through this journal. As the reader will find in this inaugural issue, we have compiled an initial set of studies across multiple methods and geographies that help to set the terms of future editions. We examine: historical political ecologies of land use around opium cultivation in the uplands of Thailand; emerging governance regimes of corporate social responsibility in Myanmar; the capacity of new state institutions to manage land conflict in forest estate lands in Indonesia; a close analysis of forest harvesting and management in a mangrove forest in Malaysia; and, an economic valuation of non-timber forest products in a national park in Indonesia. There is much to choose from and much more to delve into. We hope that this issue serves as an impetus to engage on these timely themes and further encourages new ideas for submissions.